Diet control on carbon isotopic composition of land snail shell carbonate - Liu, ZongXiu; Gu, ZhaoYan; Wu, NaiQin; Xu, Bing (Chinese science bulletin, 2007)
Carbon isotope compositions for both the carbonate shells and soft bodies （organic tissue） of living land snails collected mostly from the Loess Plateau, China have been measured. The result shows that δ^13C values range from -13.1‰ to -4.3‰ for the aragonite shell samples and from -26.8‰ to -18.0‰ for the soft body samples. Although the shells are enriched in ^13C relative to the bodies averagely by 14.2（±0.8）‰, the shell δ^13Ca values are closely correlated to the body δ^13Corg values, expressed as δ^13Ca = 1.021 δ^13Corg ＋ 14.38 （R = 0.965; N = 31）. This relationship indicates that δ^13Ca is primarily a function of the isotopic composition of the snail diets since previous studies have proved that the snail body is the same as their food in carbon isotope composition. In other words, carbon isotope composition of the carbonate shell can be used as a proxy to estimate the dietary ^13C abundance of the land snails. The data also support that the ^13C enrichment of the carbonate shells results mainly from the equilibrium fractionations between the metabolic CO2, HCO3^- in the hemolymph and shell aragonite, and partially from kinetic fractionaUons when snail shells form during their activity.